Analisis Minat Belajar Peserta Didik dalam Pembelajaran Sejarah di Kelas X SMA Negeri 16 Samarinda - Ana, Adriana; Rahuma, Aulia (STKIP PGRI SITUBONDO, 2024)
Interest in learning is the main factor that allows students to receive lessons well. When students are interested, they tend to treat their studies more seriously and give their best in every lesson. This study aims to examine students' learning interest in history lessons in Grade X at SMA Negeri 16 Samarinda and identify the factors influencing their interest in learning history. The research method employed is a qualitative approach with a case study design. Data collection techniques include observation, Likert-scale questionnaires, interviews, and documentation. The findings indicate that students' learning interests can be assessed based on four indicators: enjoyment, interest, attention, and engagement. Based on these indicators, students generally demonstrate a good interest in history lessons. However, some aspects still need improvement to enhance their overall learning interest further. Regarding the factors influencing students' learning interest in history lessons in Grade X at SMA Negeri 16 Samarinda, the internal factors include intelligence, student attitudes, motivation, and learning fatigue. Meanwhile, the external factors comprise teaching methods, family conditions, social environment, and learning facilities.